2016
DOI: 10.2214/ajr.14.14099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stereotactic Body Radiotherapy on the Growth Kinetics and Enhancement Pattern of Primary Renal Tumors

Abstract: OBJECTIVE. The objective of our study was to assess the growth rate and enhancement of renal masses before and after treatment with stereotactic body radiotherapy (SBRT). MATERIALS AND METHODS. This retrospective study included all patients with renal masses who underwent SBRT during a 5-year period. Orthogonal measurements of renal masses were obtained on pre- and posttreatment CT or MRI. Pre- and posttreatment growth rates were compared for renal mass diameter and volume using the t test. Pre- and posttrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 38 publications
(39 reference statements)
4
20
0
Order By: Relevance
“…Inherent population‐level biases may have been introduced through data sampling of widely disparate populations from Japanese, European, North American, and Australian patients. Another limitation to the interpretation of data is the local response assessment after SABR; it is unclear whether Response Evaluation Criteria in Solid Tumors should remain the optimal assessment criteria in this setting …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherent population‐level biases may have been introduced through data sampling of widely disparate populations from Japanese, European, North American, and Australian patients. Another limitation to the interpretation of data is the local response assessment after SABR; it is unclear whether Response Evaluation Criteria in Solid Tumors should remain the optimal assessment criteria in this setting …”
Section: Discussionmentioning
confidence: 99%
“…Another limitation to the interpretation of data is the local response assessment after SABR; it is unclear whether Response Evaluation Criteria in Solid Tumors should remain the optimal assessment criteria in this setting. 25 Local control, minimal complications, and preserved renal function are considered to constitute "the trifecta" after minimally invasive partial nephrectomy. 26 The current multi-institutional, pooled analysis marks an important step in demonstrating that SABR can achieve this trifecta in localized RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Standard response assessments using morphological measurements and CT based contrast enhancement criteria after SABR for primary RCC are known to be challenging. In a recent study, it was shown that tumour growth rate and tumour size were reduced in primary RCC after SABR, however no significant differences in tumour signal enhancement were shown on multiphasic contrast-enhanced MRI during the initial post treatment period [ 28 ]. The authors concluded further studies were needed to determine the correlation between tumour enhancement and disease progression and specified the need for longer follow-up times.…”
Section: Discussionmentioning
confidence: 99%
“…Within this challenging context, we sought to carry out an exploratory analysis of diffusion and perfusion changes shown by DWI and DCE MRI after SABR for primary RCC and assess whether any correlate with treatment response shown on CT. We have carried out this assessment on patients with a consistent imaging protocol, acquired on the same MR scanner which has eliminated sequence and scanner variability. We have correlated changes in MRI parameters with percentage tumour volume change from consistent CT time points, while also assessing the last follow-up CT scan which we considered suitable as tumour shrinkage over time is typically slow and relatively linear [ 28 ]. This last follow-up CT was a median 761 days (range 385–1085 days) after SABR treatment, providing a long follow-up time for the analysis (see S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the study by Sun et al. it appears that stable or partial radiological responses will predominate in the early years after SABR and, unlike thermal ablation, changes in enhancement patterns can be very slow to evolve.…”
mentioning
confidence: 60%